11.1 EXECUTIVE COGNITIVE TRAINING VS. PERCEPTUAL COGNITIVE TRAINING FOR SCHIZOPHRENIA-SPECTRUM DISORDERS: TREATMENT OUTCOMES AND PREDICTORS OF RESPONSE. (9th April 2019) - Best, Mike; Bowie, Christopher
Abstract: Background: Neurocognitive impairments are the best predictors of community functioning for individuals with schizophrenia-spectrum disorders. Cognitive remediation is a psychological intervention designed to improve neurocognitive abilities and community functioning. However, different theoretical approaches have developed without any studies directly comparing them. Additionally, with a movement towards personalizing cognitive enhancing techniques, greater emphasis is being placed on determining predictors of treatment response. The current study is the first to compare the two dominant approaches to cognitive remediation (training of executive skills and training of perceptual skills) and examine predictors of treatment response. Methods: 70 outpatients with schizophrenia-spectrum disorders were randomized to receive either 6 weeks of executive training (ET) or perceptual training (PT). Electrophysiological activity, neurocognition, functional competence, case-manager rated community functioning, clinical symptoms, and self-report measures were assessed at baseline, post-treatment, and 12-weeks post-treatment. Results: There were minimal differences between groups at the post-treatment visit. PT improved EEG mismatch negativity amplitude significantly more than ET immediately post-treatment (d = 0.64), however, the effect did not persist at 12-week follow-up (d = 0.01). Examining long-term effects, at 12-week follow-up, ET increased EEG theta power during an n-back working memory task (d = 1.01), neurocognition (d = 0.64), functional competence (d = 0.67), and case manager rated community functioning (d = 0.53) to a greater extent than PT. Larger P300 amplitude (B = .47) and theta power during a working memory task (B = .34) at baseline were significantly associated with larger improvements in neurocognition post-treatment. Baseline mismatch negativity amplitude was not significantly associated with treatment response (B = .17), and no baseline EEG measures predicted functional outcomes. Conclusions: Both PT and ET improved neurophysiological mechanisms specific to their domains of intervention, however, only ET resulted in improvement in neurocognition and functioning. Improvements in favor of ET did not appear immediately post-treatment but emerged 12 weeks after the end of active treatment. Training executive functioning may prime further cognitive and functional improvements. Executive functions may be more functionally relevant than other cognitive domains and when addressed in treatment lead to better outcomes. Greater P300 amplitude and theta power may be associated with learning-related processes which are important for acquisition and retention of skills during cognitive training programs.